Secagem de grãos de girassol em leito fixo e em leito de jorro - Evangelista Neto, Alcivan Almeida (2013)
This work studies two methods for drying sunflower grains grown in the western region of Rio Grande do Norte, in the premises of the Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte - IFRN - Campus Apodi. This initiative was made because of the harvested grain during the harvest, being stored in sheds without any control of temperature, humidity etc. Therewith, many physical, chemical and physiological characteristics are compromised and grains lose much quality for oil production as their germination power. Taking into account that most of the stored grain is used for replanting, the studied methods include drying of grains in a thin layer using an oven with air circulation (fixed bed) and drying in a spouted bed. It was studied the drying of grains in natura, i.e., newly harvested. The fixed bed drying was carried out at temperatures of 40, 50, 60 and 70°C. Experiments in spouted bed were performed based on an experimental design, 2² + 3, with three replications at the central point, where the independent variables were grains load (1500, 2000 and 2500 g) and the temperature of the inlet air (70, 80, and 90 °C), obtaining the drying and desorption equilibrium isotherms. Previously, the characteristic curves of the bed were obtained. Both in the fixed bed as in the spouted bed, drying and desorption curves were obtained by weighing the grains throughout the experiments and measurements of water activity, respectively. The grains drying in the spouted bed showed good results with significant reduction of processing time. The models of FICK and PAGE were fitted to the experimental data, models which will represent the drying of grains both in the fixed bed as in the spouted bed. The desorption curves showed no influence of the processing temperature in the hygroscopic characteristics of the grains. The models of GAB, OSWIN and LUIKOV could well represent the desorption isotherms